2020
DOI: 10.1111/1759-7714.13340
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative platelet distribution width: A predictive factor of the prognosis in patients with non‐small cell lung cancer

Abstract: Background The prognostic value of platelet distribution width (PDW) is different in various malignancies. The purpose of this study was to identify the relationship between preoperative PDW and survival in patients with non‐small cell lung cancer (NSCLC). Methods Optimal cutoff values of PDW were confirmed using a receiver operating characteristic (ROC) curve. The Kaplan‐Meier method and log‐rank test were used to estimate disease‐free survival (DFS) and overall survival (OS). Univariate and multivariate Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
3
2
1
Order By: Relevance
“…By contrast, our findings indicate that low PDWs are related to poor outcomes, which is consistent with several earlier studies (13)(14)(15)(16). Low MPV is reportedly predictive of unfavorable outcomes in diffuse large B-cell lymphoma (29), multiple myeloma (30), and lung cancer (31).…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, our findings indicate that low PDWs are related to poor outcomes, which is consistent with several earlier studies (13)(14)(15)(16). Low MPV is reportedly predictive of unfavorable outcomes in diffuse large B-cell lymphoma (29), multiple myeloma (30), and lung cancer (31).…”
Section: Discussionsupporting
confidence: 92%
“…An increase in platelet number provides a microenvironment that promotes coagulation and aggregation with tumor cells, enabling platelets to guard tumor cells and eventually cause them to escape the host immune system [36]. Our results are inconsistent with those of Liu et al [37], who analyzed 750 postoperative patients with NSCLC and found that low PDW was an independent adverse prognostic factor for DFS and OS. However, discrepancies have been observed in other studies.…”
Section: Discussioncontrasting
confidence: 96%
“…Nevertheless, the data dealing with these subjects were conflicting among studies. Low PDW has proved to be a strong correlation with poor prognosis in lung ( 28 ), colon ( 29 ), hepatocellular ( 30 ), endometrial ( 31 ), and esophageal cancers ( 32 ), which is consistent with our findings. In the genitourinary tumors, low PDW has shown to be related to more advanced stages in bladder cancer ( 33 ).…”
Section: Discussionsupporting
confidence: 91%